2013
DOI: 10.1177/0884533613486933
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of the Cut‐and‐Push Method for Removing Large‐Caliber Soft Percutaneous Endoscopic Gastrostomy Devices

Abstract: The cut-and-push method employed for removal of a soft PEG tube with a large caliber seems to be safe and can be performed when removal by external traction may determine the occurrence of peristomal complications or jeopardize PEG replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 12 publications
0
14
0
3
Order By: Relevance
“…Use of balloon‐tipped PEG tubes could minimize the potential danger of disruption of the gastrocutaneous canal. Endoscopic removal or cutting the indwelling tube and allowing disposal of the internal bumper via the gastrointestinal tract (the cut‐and‐push method 7 ) are acceptable. However, the cost‐effectiveness of endoscopy in this setting is questionable and the second alternative possesses a minimal risk of bowel obstruction, although this risk has not been detected in the largest so far, prospective study of using the cut‐and‐push method to replace PEG devices larger than 15 Fr 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Use of balloon‐tipped PEG tubes could minimize the potential danger of disruption of the gastrocutaneous canal. Endoscopic removal or cutting the indwelling tube and allowing disposal of the internal bumper via the gastrointestinal tract (the cut‐and‐push method 7 ) are acceptable. However, the cost‐effectiveness of endoscopy in this setting is questionable and the second alternative possesses a minimal risk of bowel obstruction, although this risk has not been detected in the largest so far, prospective study of using the cut‐and‐push method to replace PEG devices larger than 15 Fr 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Five cohort studies were identified that reported the use of CP in larger groups of patients (4)(5)(6)(7)(8). Of these three studies were prospective ( 4,5,8 ) and two were retrospective ( 6, 7 ).…”
Section: Cohort Studiesmentioning
confidence: 99%
“…X-ray is considered to provide unequivocal evidence of flange excretion ( 4 ) but this was only reported in 68 cases ( 4,5 ). Most frequently excretion of the flange was confirmed by visualization of the flange in the stool and was reported in 98 cases, usually by the patient or caregiver ( 4,5,8 ). Two studies reported a combination of x-ray verification and flange seen in stool ( 4, 5 ) whilst Agha ( 8 ) reported flange seen in stool.…”
Section: Cohort Studiesmentioning
confidence: 99%
See 2 more Smart Citations